An abridged history of the Greek-Italian and Greek-German War 1940-1941 : land operations - Χακά, Μαρία (An Army History Directorate editions., 1997)
This publication refers to the major war operations and the main political and diplomatic events that drastically influence the inception of the War. This issue was written based on the 19 volumes of the Army History Department and consists of four main parts. The first part describes the army-political and diplomatic events preceding the Italian attack against Greece. The second part refers to the Greek counter-attack, the advance of the Greek army and the great "Summer" Italian attack which resulted in a complete failure. The third part refers to the German attack of April 6th, 1941, the surveillance of the Metaxas Forts and the common Greek- British battles and the occupation of Greece (ex Crete). The fourth and last part refers to the battle of Crete and its occupation by the Germans. A list of all the fallen of the Greek army, along with appendices, official charts, various tables and charts of photographic material is included.